(3JaSjQ GdbQBf GdLdjd, GdeSei, dHGH GdJChjd aj eYGfj GdJfRjds - (3GdNGRf, Ydj Hf eMeO Hf EHQGgje,s 678-741 (3g`(B.s ((3HjQhJ (B:s (3OGQ GdcJH GdYdejI,s, 2004)
(3JaSjQ GdbQBf GdcQje(B.s
(3GdeMJhjGJ (B: (3eL(B. 1. (3GdJaSjQ ef Chd ShQI GdaGJMI MJi BNQ ShQI GdfSGA(B-(3eL(B. 2. (3ef Chd ShQI GdeGFOI MJi ShQI jhSa(B-(3eL(B. 3. (3ef Chd ShQI GdhYO MJi BNQ ShQI aGWQ(B-(3eL(B. 4. (3ef Chd jGSjf MJi BNQ ShQI GdfGS(B.s
Keywords: (3GdbQBfs -- (3JaGSjQs